If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X+4X=4X+1
We move all terms to the left:
X+4X-(4X+1)=0
We add all the numbers together, and all the variables
5X-(4X+1)=0
We get rid of parentheses
5X-4X-1=0
We add all the numbers together, and all the variables
X-1=0
We move all terms containing X to the left, all other terms to the right
X=1
| x-6.8=14.7 | | 5y÷2=15 | | 7.50=15/n | | 6/3r=-7/2 | | 3+2x+(-34)=11 | | t+52=3 | | 3(4x+4)+5(2x-3)=-47 | | z-1/3=1/2/3 | | -(2x+10)=90 | | x+(2x-5)=130 | | b+42=3b | | 3x-8+4x=2x+18-6x | | 3x^2+5x+56=0 | | 9(f-94)=45 | | J=5x-2 | | x+5(6-8)-4=4+5x-2 | | 193=8b^2-7 | | 9(f−94)=45 | | 2/9q=-5/8 | | n^2+18n+61=-4 | | n÷3-4=20 | | 2(y-56)=60 | | 3(-x)-2(-x)-(-4)=(-x)-x+1 | | 2(y−56)=60 | | x^2−2x−24=0 | | 96=6(n+2) | | 3-4r=-25 | | x^2−2^x−24=0 | | 5r^=80 | | 48=4(h+72) | | h2-3h=8 | | 12.3=41x |